Accelerometry-Based Digital Gait Characteristics for Classification of Parkinson's Disease: What Counts? - Rana Zia Ur Rehman; Christopher Buckley; Maria Encarna Mico-Amigo; Cameron Kirk; Michael Dunne-Willows; Claudia Mazza; Jian Qing Shi; Lisa Alcock; Lynn Rochester; Silvia Del Din (IEEE Open Journal of Engineering in Medicine and Biology)
Objective: Gait may be a useful biomarker that can be objectively measured with wearable technology to classify Parkinson's disease (PD). This study aims to: (i) comprehensively quantify a battery of commonly utilized gait digital characteristics (spatiotemporal and signal-based), and (ii) identify the best discriminative characteristics for the optimal classification of PD. Methods: Six partial least square discriminant analysis (PLS-DA) models were trained on subsets of 210 characteristics measured in 142 subjects (81 people with PD, 61 controls (CL)). Results: Models accuracy ranged between 70.42-88.73% (AUC: 78.4-94.5%) with a sensitivity of 72.84-90.12% and a specificity of 60.3-86.89%. Signal-based digital gait characteristics independently gave 87.32% accuracy. The most influential characteristics in the classification models were related to root mean square values, power spectral density, step velocity and length, gait regularity and age. Conclusions: This study highlights the importance of signal-based gait characteristics in the development of tools to help classify PD in the early stages of the disease.